2012
DOI: 10.1007/8904_2012_207
|View full text |Cite
|
Sign up to set email alerts
|

Sight-Threatening Phenylketonuric Encephalopathy in a Young Adult, Reversed by Diet

Abstract: Phenylketonuria (PKU) leads to severe neurological disorders in childhood, shunned by the diet. The long-term prognosis after diet diversification at adolescence is uncertain. We report a case of cortical blindness in a young patient regressive 1 month after the diet was resumed.Mr M., 25 years old, had PKU detected at birth. He maintained good serum levels of Phenylalanine (Phe) (120-300 μmol/L) during childhood and got a normal intellectual development. During adolescence he diversified his diet but maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Some patients who experience suboptimal outcomes and return to diet improve. In adults, the reported neurological complications ( n = 4) [ 66 ] and vision loss ( n = 2) [ 67 , 68 ] all improved or even reversed when Phe-restricted diet with Phe-free L-amino acid supplements was reinstituted [ 66 68 ]. In addition Schmidt et al [ 69 ] reported reversible effects on sustained attention and calculation speed in a trial with 15 adults.…”
Section: Initiation Of Treatment and Treatment For Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Some patients who experience suboptimal outcomes and return to diet improve. In adults, the reported neurological complications ( n = 4) [ 66 ] and vision loss ( n = 2) [ 67 , 68 ] all improved or even reversed when Phe-restricted diet with Phe-free L-amino acid supplements was reinstituted [ 66 68 ]. In addition Schmidt et al [ 69 ] reported reversible effects on sustained attention and calculation speed in a trial with 15 adults.…”
Section: Initiation Of Treatment and Treatment For Lifementioning
confidence: 99%
“…ETPKU adults usually show a clear relationship between concurrent blood Phe concentrations and certain aspects of brain function, brain metabolism and differences in myelination as summarized by van Spronsen et al [ 72 ]. Some adults who have not been treated early and continuously have been reported to develop neurological complications such as leukoencephalopathy, spastic paraparesis, brisk reflexes, tremor, Parkinsonism, psychiatric symptoms ( n = 4) [ 66 ] and vision loss ( n = 2) [ 67 , 68 ]. Tremors have also been detected in ETPKU, although they are more frequent and severe in late treated patients [ 73 ].…”
Section: Initiation Of Treatment and Treatment For Lifementioning
confidence: 99%
“…Initialement, les traitements étaient arrêtés pendant l'enfance ou au début de l'adolescence. L'apparition de complications neurologiques [25,26]…”
Section: Devenir Des Patients Phénylcétonuriquesunclassified
“…En effet, en l'absence de contrôle [43]. Des atteintes neurologiques sévères ont cependant été décrites chez certains patients qui n'avaient plus observé leur régime (avec des taux de Phé plasmatique parfois supérieurs à 1 800 µmol/L [30 mg/ dl]) : perte de la marche, épilepsie et parfois perte de la vision [27]. Ces patients peuvent néanmoins récupérer, le plus souvent totalement, après une remise à un suivi strict du régime alimentaire.…”
Section: Pcu Et Grossesseunclassified